Masjid sebagai Pusat Inovasi Pendidikan dan Pelatihan untuk Peningkatan Kualitas Masyarakat - Rifka Andriani; Putri Adillah; Winda Sugiarti; Rima Junita Putri; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This article discusses the potential role of mosques as centers for educational innovation and training to improve community capacity. Through a literature review and case study, this article aims to explore how mosques can transform from simple places of worship into comprehensive learning centers. The method used in this study is a qualitative method, by making books, magazines, articles and journals related to the research theme, focusing on innovative education and training models that can be applied in mosques, the challenges that may be faced, and their potential benefits for the community. The results of the analysis show that with the right approach, mosques can become important buildings in human resource development and community empowerment in two innovations, namely Educational Innovation; (1) Establishing non-formal educational institutions such as TPA and MDA, (2) Routine syllabus studies, (3) Arabic language course institutions. Training Innovation; (1) funeral prayer training, (2) Youth mosque leadership training, (3) Preaching training.